2015
DOI: 10.12968/bjom.2015.23.12.862
|View full text |Cite
|
Sign up to set email alerts
|

National survey of current practice standards for the newborn and infant physical examination

Abstract: Objectives: To determine compliance with recommended standards for the newborn and infant physical examination (NIPE), identify which professionals were performing the NIPE and determine standards for screening and management of babies at risk of developmental dysplasia of the hip (DDH) or congenital heart disease (CHD). Design: In autumn 2014, an online questionnaire was sent to all heads of midwifery in the UK. Key findings: Completed questionnaires were returned from 64.3% (n=99/154) of targeted NHS Trusts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The popularity of the NIPE among midwives was highlighted, with many AEIs offering a preparation programme twice a year. It was surprising, however, that despite the widespread provision and popularity of NIPE education, only 13% of UK midwives are currently NIPE-qualified (Rogers et al, 2015). One possible explanation may lie in the concerns expressed by some respondents about midwives subsequently maintaining their skills as NIPE practitioners following qualification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of the NIPE among midwives was highlighted, with many AEIs offering a preparation programme twice a year. It was surprising, however, that despite the widespread provision and popularity of NIPE education, only 13% of UK midwives are currently NIPE-qualified (Rogers et al, 2015). One possible explanation may lie in the concerns expressed by some respondents about midwives subsequently maintaining their skills as NIPE practitioners following qualification.…”
Section: Discussionmentioning
confidence: 99%
“…Townsend et al (2004) recommended that the NIPE should become part of midwives' standard practice. Eleven years after the EMREN study's proposals, a survey of all maternity units in the UK found that these recommendations were not being met (Rogers et al, 2015) and that only 13% of UK midwives were qualified NIPE practitioners; the reasons for this were not clear. The investigators, therefore, felt it important to establish a national picture of the preparation of midwives for this role.…”
Section: Introductionmentioning
confidence: 99%
“…A questionnaire was developed by a team of midwifery educationalists utilising some of the content from a tool devised from phase one of this study (Rogers et al, 2015). A pilot study was undertaken in a single AEI, after which the questionnaire, accompanying letter and instructions underwent minor modifications to improve clarity and ease of completion.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent literature illustrates a growing acceptance of midwives undertaking the NIPE as part of their enhanced role (Baker K, 2010) and observes that midwives value the accountability of including the NIPE as part of their holistic provision of care (Mcdonald, 2013). However, a national survey of current NIPE practice revealed that despite the recommendations of the EMREN study (Townsend et al, 2004) only 13.7% of UK midwives are currently NIPE trained and a high proportion of these are undertaking a significant number of NIPEs (Rogers, Jay, Yearley, & Beeton, 2015). Blake (2012) explored the potential of student midwives undertaking the NIPE as a compulsory part of their preregistration programme and thus qualifying as a NIPE practitioner at the point of registration (Blake, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation